Aluminum, at an environmental concentration, associated with acidic pH and high water temperature, causes impairment of sperm quality in the freshwater teleost Astyanax altiparanae (Teleostei: Characidae) - Silva Pinheiro, Joao Paulo; Assis, Cecilia Bertacini de; Sanches, Eduardo Antonio [UNESP]; Moreira, Renata Guimaraes (Elsevier B.V., 2020)
Given the toxicity of metals, including aluminum (Al), and the effects of water temperature on ectotherms, we investigated the individual or association effect of these variables (Al + acidic pH + temperature changes) on sperm quality of Astyanax altiparanae. Mature males were divided into nine experimental groups based on the combination of each of three water temperatures (20, 25, and 30 degrees C) with neutral and acidic pH values (7.0 and 5.5, respectively) with or without 0.5 mg L-1 Al. The fish were subjected to subacute, semi-static exposure and at 24 and 96 h were evaluated for seminal parameters: (1) pH; (2) osmolality; (3) sperm concentration; (4) sperm morphology; (5) sperm kinetics; and (6) sperm ultrastructure. At 30 degrees C, Al caused a reduction in osmolality (24 and 96 h) and sperm concentration (24 h). When analysing sperm kinetics (30 s post-activation), Al caused a reduction in total motility at all temperatures (24 h), and when this exposure time was longer (96 h), both acidic pH and Al addition to the water caused sperm motility reduction. By analysing curvilinear velocity (VCL) 30 s after sperm activation (24 and 96 h), the acidic pH caused a reduction in sperm movement at 20 and 30 degrees C, but at 25 degrees C Al triggered this reduction. Finally, Al in the water caused ultrastructural changes in the sperm head, midpiece, and flagella regardless of water temperature. Also, it was found that the combination of Al at 30 degrees C caused a reduction in sperm head area while at 20 degrees C, Al triggered a reduction in the midpiece area. Therefore, acidity influenced some A. altiparanae sperm parameters but Al in the water accentuated these effects on seminal quality, especially seminal osmolality and sperm concentration, kinetics, and ultrastructure. This toxicity was also influenced by changes in water temperature. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Fish; Metal; Reproduction; Spermatozoa; Subacute exposure